THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS INMANAGINGACTIVE, EFFECTIVE AND FUN CLASSES AT SMPN5 - Nurhaliza, Indriyani; Putra, Safril Aditia; Musyarofah, Nurul Fitriya; Faradila, Afifah Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to determine how teachers manage the classroomtocreate optimal learning conditions at SMPN 5 Pamekasan. This research uses qualitative research. Data collection is done throughobservation, interviews. Based on the results of the study, it can be concluded that the role of Islamic Religious Education teachers inmanaging active, effective, and fun classes at SMPN 5 Pamekasan is that teachers must be able to organize, implement, and assess students in order to have tactics in mastering the class so that SMPN5 Pamekasan teachers understand children's learning power, so that efforts to achieve the success of learning objectives require teacher skills in managing the classroom so that the learning process allows students to learn. SMPN 5 Pamekasan has an active Islamic religious education teacher in the classroom who can provide examples tostudents to behave well, can apply various learning methods such as group discussions and inquiry-based learning approaches.